Pemikiran Zakiah Daradjat Antara Kesehatan Mental dan Pendidikan Karakter - Sri Indah (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2020)
This library research aimed to find the point of integration between mental health and character education. The dynamics of Islamic study is presecuted to develop the paradigm unity of Islamic study, exact sciences and humanities. This research try to contribute pedagogic by intergrating mental health science with Tafseer. Hopefully the intergration of mental health science gives the steady in conception in understanding of human dynamics. Integration with Tafseer meant to find originality in Islam. So this research is able to find the concept of comprehensive, holistic, in depth and applicable in the world of education. This is a qualitative research that used informaton from Al-Qur’an, Al-Hadis, books of mental health experts and character education experts. The documentation method was used to collect the data of research. This research try to reveal and to ta’shil the understanding of mental, mental health and tazkiyah nafs then aplicate this understanding into character education. The result of the research indicates that tazkiyah nafs is the point of integration between mental health and character education for building healthy and characteristic individual